Boiling : research and advances - Koizumi, Yasuo; Shoji, Masahiro; Monde, Masanori; Takata, Yasuyuki; Nagai, Niro (Elsevier, 2017)
This book presents the latest developments and improvements in the technologies, instrumentation, and equipment surrounding boiling.